(untitled) (Research, Society and Development, 2021)
The SARS-CoV-2 pandemic affected the quality of life (QL) of healthcare professionals. This study verifies the quality of life of physical therapists who have been working in hospitals in Santa Catarina since the beginning of the COVID-19 pandemic. This is a study with a quantitative and descriptive approach, survey research procedure and closed questionnaire technique. The QWLQ-bref is used, an abbreviated version of an instrument that aims to measure QWL in four domains: physical, psychological, personal and professional of physiotherapists working in hospitals in a city in Santa Catarina. The research results show that in the physical domain, quality of life had a considerable drop in the following items: sleep, physiological needs and work environment. In the psychological domain, respondents indicated that they were more insecure, but more proud of their profession. In the personal domain, there is an increase in items related to: work relationships, family and respect for colleagues. Regarding the professional domain, quality of life is classified as low and very low. Thus, it is concluded that during this period of pandemic there was a drop in the quality of life of physiotherapy professionals working in hospital institutions.